Prototipe Sistem E-Learning dengan Pendekatan Gaya Belajar VARK (Kasus: Politeknik Indramayu) - Eka Ismantohadi; Lukito Edi Nugroho; Sri Suning Kusumawardani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
The process of forming knowledge on school or college learning for each student has different characteristics. In the learning process, there are learners with capability to memorize, and then shape it into visual knowledge, while the others can easily recall the information and shape it into aural knowledge and also ability to read/write and to learn practice into kinesthetic ability. Basically, every individual has various learning styles, but they may dominant and has a tendency to a particular learning styleThis study tries to build a prototype of E-learning system to identify the characteristics of students learning styles using Visual, Audio, Read and Kinesthetic (VARK) approach. The results of this identification will also provide recommendations in accordance with the materials needed suitable with the learning styles of each student. This will help students to easily understand the learning materials. This study was constructed in a web-based system using PHP and MySQL.The results indicated that the system can identify the students learning styles by filling out a questionnaire with VARK approach to find out the best learning style suitable to them based on VARK approach. In addition, this system also gives course material recommendations based on the learning styles of VARK approach.